The impact of family environment, self-concept, and school attitude on 9th grade students' academic achievement - Bölükbaşı, Beyza. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
The study aims to investigate the predictor role of family environment, self-concept, and school attitude on children's academic achievement. The sample of the study consists of 288 (133 girls/155 boys) students in grade 9 who are enrolled in two public high schools of middle SES level. Each participant provided self-report data that included general demographic information, as well as the Turkish version of family environment, self-concept, and school attitude measures. For the data analysis, Pearson correlation, multiple regression simultaneously, and one-way ANOVA procedures were utilized.Findings from the study indicate that among the three independent variables, namely family environment, measured by the Family Environment Questionnaire (FEQ, Fowler,1980), self-concept, measured by the Piers-Harris Self-concept Scale (WIFAM, Piers-Harris, 1969), and school attitude, measured by the School Attitude Assessment Survey-Revised (SAAS-R, McCoach, 2000), the best predictor of academic achievement is attitude towards school (r=.22). The findings suggest that it is possible to improve 9th grade students' academic achievement by helping them to develop a positive attitude towards school.
Keywords: Academic achievement.; Self-perception in children.; Home and school.